A dynamic singular equation system of asset demand - Joachim Zietz; Ronald Weichert (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
The paper presents estimates of a dynamic demand system of the AIDS type for financial assets. The results suggest that dynamic behavior plays a major role in determining asset demand. Estimates on the basis of the equivalent static equilibrium models prove to be clearly inferior statistically. Also, the theoretical restrictions of homogeneity and symmetry are thoroughly rejected by the static model versions, however, not by the dynamic demand system. The cross rate elasticities between bonds and savings deposits and also between money and time deposits are found to be negligible for Germany. Time deposits turn out to be very sensitive to own and cross rates of return.
Keywords: 330